Image and Graphics 8th International Conference, ICIG 2015, Tianjin, China, August 13-16, 2015, Proceedings, Part II - Zhang, Yu-Jin (Image Processing, Computer Vision, Pattern Recognition, and Graphics ;, 2015)
This book constitutes the refereed conference proceedings of the 8th International Conference on Image and Graphics, ICIG 2015 held in Tianjin, China, in August 2015. The 164 revised full papers and 6 special issue papers were carefully reviewed and selected from 339 submissions. The papers focus on various advances of theory, techniques and algorithms in the fields of images and graphics.